Student’s Perspectives on Augmented Reality in Pharmacy Education in Hong Kong - Li, Joyce Tik Sze; Ng, Enoch E Nok; Lee, Vivian Wing Yan (Frontiers in Education, 2021)
Introduction: Augmented reality (AR) technology has demonstrated potential on various areas of healthcare practice. Its role on medical education is starting to emerge. This study aimed to investigate students’ perspectives on using AR as learning tools in undergraduate pharmacy education. Methods: Four AR micro modules on post-stroke management and chronic obstructive pulmonary disease (COPD) were developed for third year undergraduate pharmacy students to study. Students played the role of pharmacists in the AR micro modules. They collected information to identify patients’ chief complaints, history, risk factors, comorbidities, and other problems, and provided recommendation on patients’ treatment plans. Teacher guided the discussions and addressed students’ enquiries. Students’ feedback was collected by pre- and post-intervention survey. Results: A total of 54 students participated in the current study. The was no significant change in students’ perceived knowledge on post-stroke management and COPD, as well as their confidence in providing patient counselling on relevant topics. Students expressed that their learning experience with AR was not positive. Technical problems were the major difficulties that students encountered. Conclusion: There was no significant difference in pharmacy students perceived clinical knowledge and confidence on patients’ counselling after completing the AR modules. Technical issues were the major hurdles that hindered students’ learning experience with AR.